Long-Term Safety and Efficacy Data of a Plasma-Derived Factor VIII Concentrate with von Willebrand Factor for Treatment of Patients with Hemophilia A Covering 18 Years - Kittler, Sabine Friederike Karolin; Miesbach, Wolfgang; Bauhofer, Artur; Becker, Thomas; Schüttrumpf, Jörg; Dubovy, Patrick; Nemes, László; Richter, Heinrich; Königs, Christoph (Hämostaseologie, 2019)
We describe the results of the (to our knowledge) longest long-term noninterventional study so far performed to obtain real-life data on the treatment of hemophilia A patients with a single plasma-derived FVIII concentrate containing von Willebrand factor (pdFVIII; Haemoctin/Faktor VIII SDH Intersero). A total of 198 patients (146 in Germany and 52 in Hungary), of whom 160 had severe and 38 nonsevere hemophilia A, representing all age groups (0–88 years; mean ∼25 years at inclusion) were analyzed during prophylactic or on-demand treatment over 18 years (overall 1,418 patient-years; mean >7 years). pdFVIII was very effective and well tolerated. The mean annual bleeding rate, including spontaneous and traumatic bleeds, was considerably lower for patients treated prophylactically (mean 5.4; median 3.1) than for patients treated on demand (mean 26.1; median 21.9). Inhibitors were found in 13% (3/23) and high-titer inhibitors in 4% (1/23) of previously untreated patients with severe hemophilia A. Four previously treated patients with severe hemophilia A developed inhibitors, thereof three high-titer inhibitors (3.3 and 2.5 high-titer inhibitors in 1,000 patient-years). No unexpected adverse effect on the health of the patients, no pdFVIII-related thrombosis, thromboembolic event, or hypersensitivity reaction, and no suspected viral transmission related to pdFVIII were documented.
Keywords: hemophilia A; plasma-derived factor VIII; FVIII inhibitor; noninterventional study